1999
DOI: 10.2527/1999.772311x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass traits of early-weaned steers receiving either a pasture growing period or a finishing diet at weaning.

Abstract: A 2-yr study was conducted to evaluate 1) steers fed ad libitum high concentrate after weaning (CONC), or 2) steers grown on pasture for 82 d, followed by high-concentrate finishing (PAST), on the performance and carcass traits of 74 early-weaned (117 d of age) steers. Potential breed differences were evaluated using crossbred steers of three types: 1) 3/4 Angus x 1/4 Simmental (BRI), 2) 3/4 Simmental x 1/4 Angus (CON), and 3) 1/2 Wagyu x 1/4 Angus x 1/4 Simmental (WAG). Steers were randomly assigned within br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 0 publications
9
36
0
3
Order By: Relevance
“…This is in agreement with other studies comparing beef from steers exclusively fed high grain diets vs. cattle consuming alfalfa silage ad libitum or cattle backgrounded on pasture (Myers et al 1999) followed by high grain finishing. In contrast, Dikeman et al (1985) reported higher shear scores for steers that were backgrounded before finishing vs. steers directly finished on grain.…”
Section: Shear Force and Trained Panel Sensory Evaluation Longissimussupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with other studies comparing beef from steers exclusively fed high grain diets vs. cattle consuming alfalfa silage ad libitum or cattle backgrounded on pasture (Myers et al 1999) followed by high grain finishing. In contrast, Dikeman et al (1985) reported higher shear scores for steers that were backgrounded before finishing vs. steers directly finished on grain.…”
Section: Shear Force and Trained Panel Sensory Evaluation Longissimussupporting
confidence: 93%
“…Age and weight at start of test and weight at slaughter were similar (P > 0.36) between management strategies. Weight at slaughter was also not affected in previous studies comparing steers fed a high grain diet vs. steers initially consuming alfalfa silage ad libitum or grazed on pasture before high grain finishing (Myers et al 1999). In contrast, other researchers (Rompala et al 1984;Vaage et al 1998) reported heavier slaughter weights in backgrounded cattle when compared with cattle started on a high grain diet after weaning and slaughtered at a common backfat endpoint.…”
Section: Performance and Carcass Traitsmentioning
confidence: 83%
See 1 more Smart Citation
“…Este provável aumento da capacidade digestiva deve ter sido um dos fatores que colaboraram para o maior consumo de matéria seca dos animais do T 210 durante a terminação. Myers et al (1999) concluíram que animais desmamados precocemente (117 dias) e mantidos em pastagem por 82 dias apresentaram maiores peso do retículo-rúmen e consumo de alimentos durante a fase de terminação em confinamento que animais submetidos a confinamento logo após o desmame.…”
Section: Resultsunclassified
“…Já Myers et al (1999) observaram maior GMD e melhor CA em animais também desmamados precocemente e abatidos com idade similar à do presente experimento, porém com níveis mais altos de concentrado na dieta.…”
Section: Resultsunclassified